Analisis Perbedaan Kadar Ureum dan Kreatinin dalam Serum dan Plasma pada Pasien dengan Gagal Ginjal di RSU Indah Bagan Batu - Rozi, Sihab Fahrul; Suharsih, Suharsih; Febriantika, Febriantika; Parinduri, Junaidi (Mahesa Research Center, 2025)
Urea and creatinine serve as key indicators in the evaluation of kidney function. Measurement of urea and creatinine levels can be performed using either serum or plasma. This study aims to compare the results of urea and creatinine level examinations obtained from serum and plasma in patients with kidney failure at RSU Indah Bagan Batu. The research method used is descriptive observational with a cross-sectional approach. The study sample consisted of 22 kidney failure patients who underwent urea and creatinine level examinations using an enzymatic method with an automatic analyzer. The results showed that the average urea level in serum was 186.7 mg/dL, while in plasma, it was 184.9 mg/dL, with a p-value of 0.917 (p 0.05), indicating no significant difference. Similarly, the average creatinine level in serum was 14.17 mg/dL, while in plasma, it was 14.15 mg/dL, with a p-value of 0.988 (p 0.05). Based on these findings, it can be concluded that urea and creatinine level examinations can be conducted using either serum or plasma without significant differences in the results.